Fc Receptor-Like 6 (FCRL6) Discloses Progenitor B Cell Heterogeneity That Correlates With Pre-BCR Dependent and Independent Pathways of Natural Antibody Selection - Honjo, Kazuhito; Won, Woong-Jai; King, Rodney G.; Ianov, Lara; Crossman, David K.; Easlick, Juliet L.; Shakhmatov, Mikhail A.; Khass, Mohamed; Vale, Andre M.; Stephan, Robert P.; Li, Ran; Davis, Randall S. (Frontiers in Immunology, 2020)
B-1a cells produce ‘natural’ antibodies (Abs) to neutralize pathogens and clear neo self-antigens, but the fundamental selection mechanisms that shape their polyreactive repertoires are poorly understood. Here, we identified a B cell progenitor subset defined by Fc receptor-like 6 (FCRL6) expression, harboring innate-like defense, migration, and differentiation properties conducive for natural Ab generation. Compared to FCRL6- pro B cells, the repressed mitotic, DNA damage repair, and signaling activity of FCRL6+ progenitors, yielded VH repertoires with biased distal Ighv segment accessibility, constrained diversity, and hydrophobic and charged CDR-H3 sequences. Beyond nascent autoreactivity, VH11 productivity, which predominates phosphatidylcholine-specific B-1a B cell receptors (BCRs), was higher for FCRL6+ cells as was pre-BCR formation, which was required for Myc induction and VH11, but not VH12, B-1a development. Thus, FCRL6 revealed unexpected heterogeneity in the developmental origins, regulation, and selection of natural Abs at the pre-BCR checkpoint with implications for autoimmunity and lymphoproliferative disorders.